CcpA-Dependent Carbon Catabolite Repression Regulates Fructooligosaccharides Metabolism in Lactobacillus plantarum - Chen, Chen; Lu, Yanqing; Wang, Linlin; Yu, Haiyan; Tian, Huaixiang (Frontiers in Microbiology, 2018)
Fructooligosaccharides (FOS) metabolism in Lactobacillus plantarum is controlled by two gene clusters, and the global regulator catabolite control protein A (CcpA) may be involved in the regulation. To understand the mechanism, this study focused on the regulation relationships of CcpA towards target genes and the binding effects on the catabolite responsive element (cre). First, reverse transcription-PCR analysis of the transcriptional organization of the FOS-related gene clusters showed that they were organized in three independent polycistronic units. Diauxic growth, hierarchical utilization of carbohydrates and repression of FOS-related genes were observed in cultures containing FOS and glucose, suggesting carbon catabolite repression (CCR) control in FOS utilization. Knockout of ccpA gene eliminated these phenomena, indicating the principal role of this gene in CCR of FOS metabolism. Furthermore, six potential cre sites for CcpA binding were predicted in the regions of putative promoters of the two clusters. Direct binding was confirmed by electrophoretic mobility shift assays (EMSAs) in vitro and chromatin immunoprecipitation (ChIP) in vivo. The results of the above studies suggest that CcpA is a vital regulator of FOS metabolism in L. plantarum and that CcpA-dependent CCR regulates FOS metabolism through the direct binding of CcpA towards the cre sites in the promoter regions of FOS-related clusters.